E-Module Using a Problem Based Learning Approach in Social and Science Learning of Fourth Grade Elementary Schools - Firdaus, Mohammad Hendra; Tegeh, I Made (Journal for Lesson and Learning Studies, 2024)
The lack of digital-based teaching materials makes students feel bored in learning. This causes student learning outcomes to be low. This research aims to analyze the effectiveness of E-modules using a Problem Based Learning approach in class IV science course content. The subjects of media effectiveness were 28 class IV students. The development model used is ADDIE (analyze, design, development, implementation and evaluation). The data collection methods and instruments used in this research are questionnaire methods and objective tests in the form of multiple choices. The data analysis techniques used are quantitative descriptive and inferential analysis. The results of the feasibility and practicality of the media by experts and respondents received very good qualifications and were suitable for use. The results of the effectiveness test state that H1 is accepted and H0 is rejected, so it can be concluded that the development of the E-module using the Problem Based Learning approach that was developed is effective and suitable for use by class IV students. The implication of this research is that it is hoped that it will be able to provide a reference for teachers in developing innovative teaching materials.